Guía de prácticas virtuales como recurso didáctico que apoye el proceso enseñanza - aprendizaje de química, de primer año de bachillerato paralelo “a” del colegio de bachillerato Vilcabamba, período 2016-2017. - Morocho Cumbicus, Rosa Yesenia (2018)
Chemistry is a complex science that allows to understand in detail many of the facts of nature, is not isolated from other experimental sciences; on the contrary, it has allowed the explanation of various processes in an integral way in areas vital to man. Its teaching is important, because the student is like an active processor of information, because it transforms and structures it, generating significant learning, not memory. The present titled thesis: It GUIDES OF PRACTICAL VIRTUAL AS DIDACTIC RESOURCE THAT SUPPORTS THE PROCESS TEACHING - LEARNING OF CHEMISTRY, OF FIRST YEAR OF PARALLEL HIGH SCHOOL “A” OF THE SCHOOL OF HIGH SCHOOL “VILCABAMBA”, PERIOD 2016-2017, it has as general objective: to elaborate a guide of practical virtual as didactic resource that supports the process teachinglearning of the practices of laboratory of Chemistry in the students first year of parallel High school “A” of the school of High school “Vilcabamba.” For the present investigation, the following methods were used; it is the inductive; which facilitated the obtaining of the information in students’ direct way and teacher to establish the problematic one and later to proceed to obtain the necessary information; the analytic uses it to him to know the nature of the problem and to elaborate the conclusions, also, it was tabulated results that they are represented by means of squares and graphics. The techniques that were applied were the direct observation, the interview applied to the teacher one and the survey applied the students of the First Year of parallel High school “A” of the School of High school “Vilcabamba”, the same ones that were carried out through the questionnaire. In the investigation they participated 1 teacher and 32 students. 5 The following results were obtained: The “Vilcabamba” Baccalaureate School does not have a properly equipped chemistry laboratory; The virtual practice guide was effective because when performing a previous test and contrasting it with the final test, an improvement in the average was observed, which helped to strengthen the teaching-learning process. Finally, the experiments carried out allowed students to develop the skills and abilities required in the Chemistry course